Absent or Excessive Corpus Luteum Number Is Associated With Altered Maternal Vascular Health in Early Pregnancy. Issue 3 (March 2019) - von Versen-Höynck, Frauke; Narasimhan, Purnima; Selamet Tierney, Elif Seda; Martinez, Nadine; Conrad, Kirk P.; Baker, Valerie L.; Winn, Virginia D.
Abstract : Identifying modifiable factors that contribute to preeclampsia risk associated with assisted reproduction can improve maternal health. Vascular dysfunction predates clinical presentation of preeclampsia. Therefore, we examined if a nonphysiological hormonal milieu, a modifiable state, affects maternal vascular health in early pregnancy. Blood pressure, endothelial function, circulating endothelial progenitor cell numbers, lipid levels, and corpus luteum (CL) hormones were compared in a prospective cohort of women with infertility history based on number of CL: 0 CL (programmed frozen embryo transfer [FET], N=18); 1 CL (spontaneous conception [N=16] and natural cycle FET [N=12]); or >3 CL associated with in vitro fertilization [N=11]. Women with 0 or >3 CL lacked the drop in mean arterial blood pressure compared with those with 1 CL (both P =0.05). Reactive hyperemia index was impaired in women with 0 CL compared with 1 CL ( P =0.04) while baseline pulse wave amplitude was higher with > 3 CL compared with 1 CL ( P =0.01) or 0 CL ( P =0.01). Comparing only FET cycles, a lower reactive hyperemia index and a higher augmentation index is noted in FETs with suppressed CL compared with FETs in a natural cycle (both P =0.03). The number of angiogenic and nonangiogenic circulating endothelial progenitor cell numbers was lower in the absence of a CL in FETs ( P =0.01 and P =0.03). Vascular health in early pregnancy is altered in women with aberrant numbers of CL (0 or >3) and might represent insufficient cardiovascular adaptation contributing to an increased risk of preeclampsia. Abstract : Supplemental Digital Content is available in the text.